An efficient catalytic method for the synthesis of pyrido[2, 3‐d]pyrimidines as biologically drug candidates by using novel magnetic nanoparticles as a reusable catalyst. (30th October 2017) - Moradi, Saeid; Zolfigol, Mohammad Ali; Zarei, Mahmoud; Alonso, Diego A.; Khoshnood, Abbas; Tajally, Aria
Abstract : A convenient method for the synthesis of pyrido[2, 3‐ d ]pyrimidines by using the novel nano‐magnetic silica‐bonded S ‐sulfonic acid[Fe3 O4 @SiO2 @(CH2 )3 S–SO3 H] as an efficient and recyclable catalyst under neat conditions is described. The major advantages of the present methodology are high yield, short reaction time, and reusability of the catalyst. Furthermore, the nano‐magnetic silica‐bonded S ‐sulfonic acid was fully characterized by using various techniques such as FT‐IR, TG/DTG, DTA, EDX, μXRF, XRD, HRTEM, SEM, SEM elemental mapping, XPS, and N2 physisorption. The results obtained from this research support the idea of rational design, synthesis, and applications of task‐specific and reusable catalysts for the preparation of various polynitrogenated heterocyclic compounds containing 1, 4‐dihydropyridine moieties. Abstract : A convenient method for the synthesis of pyrido[2, 3‐d]pyrimidines by using the novel nano‐magnetic silica‐bonded S‐sulfonic acid[Fe3 O4 @SiO2 @(CH2 )3S–SO3 H] as an efficient and recyclable catalyst under neat conditions is described. The major advantages of the present methodology are high yield, short reaction time, and reusability of the catalyst.